HONG KONG SAR IMMIGRATION IN THE DYNAMICS OF POLITICS, POLICY AND INSTITUTION - Andry Indrady (Jurnal Ilmiah Kajian Keimigrasian, 2018)
The Bureaucratic System of the Immigration Department of Hong Kong SAR is one of the legacies from British Colonial Government seen from legal and also immigration bureaucratic perspectives reflect the executive power domination over immigration policymaking. This is understandable since Hong Kong SAR adopts “Administrative State Model” which means Immigration Officer as a bureaucrat holds significant roles at both stages of policymaking and also its implementation. This research looks at transition period of the Immigration Department and its policies since the period of handover of Hong Kong SAR from the British Government to the Government of China especially throughout the concern from the public including academics about the future of immigration policies made by the Department that arguably from colonial to current being used as political and control tools to safeguard the interest of the Ruler. This situation ultimately will question the existence of Hong Kong SAR as one of the International Hub in the Era of Millennium.